Proceedings of the GRAPPA 2022 executive retreat - Ng, B; Jadon, D; Adebajo, A; Ayan, G; Callis Duffin, K; Chandran, V; Coates, LC; D’Agostino, MA; de Vlam, K; Deodhar, A; Eder, L; Garg, A; et al. (Journal of Rheumatology, 2023)
The Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) leadership congregated for a strategic planning meeting before the 2022 GRAPPA annual meeting in New York, USA. Meeting aims were to review GRAPPA’s performance in relation to its 2016 goals and identify successes and areas for further improvement, identify key GRAPPA priorities and activities for the next 5 years, and explore committee structures to best support these aims.